ANALISIS PENGETAHUAN LANSIA TERHADAP PEMENUHAN PERSONAL HYGIENE DI PUSKESMAS WERDHI AGUNG - Soleman, Sitti Rahma; Mongkau, Fernando M.; Ekasuryadinata, Ida Bagus (Coping: Community of Publishing in Nursing; Vol 9 No 1 (2021): Februari 2021DO - 10.24843/coping.2021.v09.i01.p10, 2021)
According to WHO, the highest status of elderly is in mainland ASIA, the number predicted to be the highest in the world, which is 400 million people or ½ of the world's elderly. Indonesia is one of the ASIA regions where the number of elderly people has increased by 0.89%. A large number of elderly people in Indonesia is one of the impacts of increasing the life expectancy of the Indonesian people. This research is a quantitative type with a descriptive approach using cross-sectional methods. Held in June-July 2020 at the Werdhi Agung Puskesmas, with a population of 158 elderly people, and a sample of 32 with purposive sampling method. This research was conducted to determine the relationship between the level of knowledge of the elderly with personal hygiene. The results showed that there was a significant relationship between the knowledge of the elderly and the personal hygiene behavior performed by the elderly. The low knowledge of the elderly about personal hygiene behavior in the working area of ??Werdhi Agung Community Health Center is the main cause of the elderly who do not have sufficient health and welfare status. Knowledge is one of the main factors of several factors that can change and motivate health behavior, while knowledge is influenced by age and education.